Immobilization rapidly selects for chemoresistant ovarian cancer cells with enhanced ability to enter dormancy. Issue 10 (9th July 2020) - Lam, Tiffany; Aguirre‐Ghiso, Julio A.; Geller, Melissa A.; Aksan, Alptekin; Azarin, Samira M.
Abstract: Around 20–30% of ovarian cancer patients exhibit chemoresistance, but there are currently no methods to predict whether a patient will respond to chemotherapy. Here, we discovered that chemoresistant ovarian cancer cells exhibit enhanced survival in a quiescent state upon experiencing the stress of physical confinement. When immobilized in stiff silica gels, most ovarian cancer cells die within days, but surviving cells exhibit hallmarks of single‐cell dormancy. Upon extraction from gels, the cells resume proliferation but demonstrate enhanced viability upon reimmobilization, indicating that initial immobilization selects for cells with a higher propensity to enter dormancy. RNA‐seq analysis of the extracted cells shows they have signaling responses similar to cells surviving cisplatin treatment, and in comparison to chemoresistant patient cohorts, they share differentially expressed genes that are associated with platinum‐resistance pathways. Furthermore, these extracted cells demonstrate greater resistance to cisplatin and paclitaxel, despite being proliferative. In contrast, serum starvation and hypoxia could not effectively select for chemoresistant cells upon removal of the environmental stress. These findings demonstrate that ovarian cancer chemoresistance and the ability to enter dormancy are linked, and immobilization rapidly distinguishes chemoresistant cells. This platform could be suitable for mechanistic studies, drug development, or as a clinical diagnostic tool. Abstract : Stiff yet porous silica‐based gels were used to immobilize ovarian cancer cells, and the cells that persisted under physical confinement exhibited hallmarks of dormancy. The authors further demonstrated that cells which survived immobilization were less susceptible to drug treatment upon removal from gels. The stress of the silica gel environment was also able distinguish ovarian cancer cells with enhanced chemoresistance, as indicated by increased survival relative to chemosensitive cells.